Chaos and frequency transformation in systems of coupled oscillators - Buts, V.A.; Vavriv, D.M.; Tarasov, D.V. (Радіофізика та електроніка, 2013)
Chaotic instabilities and frequency transformations caused by the interaction of oscillators are important effects for many applications. We review these effects from the point of view of their influence on the dynamics of practical electronic systems. It is demonstrated that the interaction of high-frequency (HF) and low-frequency (LF) oscillations can result in the development of chaotic oscillations even in the quasilinear limit creating a threat for the stability of many electronic devices. This result is illustrated by considering the destruction of both trains of pulses in a nonlinear RLC-circuit and a harmonic oscillation in a two-mode system. In its turn, the LF to HF transformations that occur in multi-mode systems can be used for the development of novel types of generators. We illustrate this approach by considering the dynamics of an ensemble of linear oscillators with controlled coupling. A possible practical realization of such generator by using an antenna array is proposed.